MANAJEMEN LABA SERTA RESPON PASAR YANG TERJADI PADA EVENT PERGANTIAN CEO - Dharma Patni, Tri Nindya; Sujana, I Ketut (E-Jurnal Akuntansi, 2016)
The purposet of this research is to find empirical evidence of earnings management at the end CEO tenure. Then, to prove the existence of difference of market response on earnings management that occurred around CEO turnover. The sample used in this study was 39 manufacturing companies in the Indonesia Stock Exchange that fit to criteria of the study sample. In this study, earnings management is proxied by Modified Jones model and tested using the independent sample t-test. Meanwhile, the market response is proxied by commulative abnormal return and tested using paired sample t-test. Results of the study found that the case earnings management by increasing profits occured at the end of CEO tenure. Then, this study obtained results that there is no difference in market response around the event of CEO turnover.
Keywords: earnings management, CEO turnover, and market response